PEMBELAJARAN BAHASA DAN SASTRA INDONESIA DI ERA REVOLUSI INDUSTRI 4.0 - Jemmi Polii (STT Bethel The Way, 2020)
This paper aims to provide an understanding of the Industrial Revolution 4.0, and provide a SWOT analysis of language and literature learning in the era of the Industrial Revolution 4.0. The method used in this study is a qualitative descriptive method with content analysis techniques. The results of the study, that the industrial revolution 4.0 has driven the automation system in all activity processes. Internet technology is increasingly massive (something that happens on a large and wide scale), not only connecting millions of people around the world, but also has become the basis for online trade and transportation transactions. The era of Industrial 4.0is an era of disruption. This phenomenon develops in changing patterns of the business world. The presence of the industrial revolution 4.0 which is based on cyber-physical systems has changed our lives. Artificial intelligence, internet ofthings, printing, robots, and intelligent machines have massively replaced human labor. In conclusion, through the SWOT analysis, it is found that there are strengths, weaknesses, opportunities and threats / challenges of Indonesian language and literature in the face of the Industrial Revolution 4.0 and Society 5.0, especially in creating entrepreneurial opportunities based on Indonesian language and literature. The solution that can be taken is the diversification of language and literature skills based on technology, information, industry and humanization.